Variabel Keragaman Produk dan Lokasi yang Mempengaruhi Keputusan Berbelanja Konsumen - Teguh Widodo (Akutansi Bisnis & Manajemen ( ABM ), 2015)
Lots of companies are trying to take advantage of business opportunities that exist with the right marketing strategy. Seeing the business world is increasingly rapidly followed by increasing competition in today's business makes the company had to rethink the company's marketing strategy is critical. This study aims to determine the effect of the diversity of products and location toward consumer shopping decisions. Data was collected by distributing questionnaires, a study conducted on 100 respondents in the sample of consumers who shop in Alfamidi Jl. Soekarno Hatta in Malang. The results showed that the diversity of products (X1) and location (X2) simultaneously significant effect on consumer decision variables shopping (Y). From R2 value indicates that consumers shopping for the decision variables (Y) is explained by diversity of products (X1) and location variable (X2), while the remaining explained by other variables beyond independent variables studied.